Criteria to assess the interdisciplinary research development: an issue formulation - Yu. D. Prokof’Eva (Библиосфера, 2018)
Scientometric studies have become an integral part of scientific libraries activities with introducing the state rating system in Russian science. Scientometric studies contribute to study long-term trends in the science development, help to discover interdisciplinary links between publications of scientists from various scientific organizations and different countries, and are a tool to determine the return and payback of public finances investments in science and research projects. Evaluation of scientists’ productivity, contribution of them and scientific organizations to the development of specific field of science or interdisciplinary research is one of the most important theoretical and applied problems in the science of science. Nowadays there is no clear methodology to assess the results of scientific activities in Russia, and all conclusions are based primarily on digital scientometric indicators, such as the number of the author’s publications and references to his work. The study objective is to determine which of the existing criteria, in combination with generally accepted indicators, can serve as a basis to form an idea about the level of contribution of organizations and authors to the interdisciplinary research development. The study has determined the boundaries of monitoring: 1. The level of organizations - scientific institutions of the Ural Federal District. 2. Time coverage: 2000-2018. 3. Subjects of the organizations under study: mathematics, mechanics and computer science; economic sciences; physical and technical sciences; chemical sciences; biological sciences; medical sciences; earth sciences; humanities; agricultural sciences; interdisciplinary problems. Research platforms are Web of Science and Scopus. In accordance with the systems approach principles, the author selects the following evaluation parameters: institute publications amount; documents types; years of publications for the whole period; leading authors; leading research directions; areas with low publications amount; co-sponsoring countries. Selected parameters tend to develop, grow and change, contribute to the information accumulation, further comparative analysis, reflect many scenarios when comparing the criteria. The author reveals a number of problems arising during the information collecting and analyzing: lack of organization profiles; incorrect affiliation; lack of a generally accepted form of words abbreviation in organization names; submitting the information on publications in the account of several organizations; a trouble of accounting the co-authors contribution to the scientific activity results.